2021
DOI: 10.1002/fld.4996
|View full text |Cite
|
Sign up to set email alerts
|

A scalable parallel unstructured finite volume lattice Boltzmann method for three‐dimensional incompressible flow simulations

Abstract: The standard lattice Boltzmann method, which employs certain regular lattices coupled with discrete velocities as the computational grid, is limited in its flexibility to simulate flows in irregular geometries. To simulate large-scale complex flows, we present a cell-centered finite volume lattice Boltzmann method for incompressible flows on three-dimensional (3D) unstructured grids and its corresponding parallel algorithm. The advective fluxes are calculated by the low-diffusion Roe scheme, and the gradients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Figure 20 shows the streamline diagram of the flow-pass sphere in the 3D flow field. For the details of the flow geometry and mechanical properties, the length X s of the recirculation region and the drag coefficient C d were selected to compare the simulation results with the previous results of A. Gilmanov et al [53] and Lei Xu et al [54] who adopted a general reconstruction algorithm with complex 3D immersed boundaries on Cartesian grids and a scalable parallel unstructured finite-volume LBM, respectively (see Figure 21). It can be concluded that as the Reynolds number increased, the recirculation region volume became larger, and the drag coefficient decreased.…”
Section: Flow Past a Sphere In Three-dimensionalmentioning
confidence: 99%
“…Figure 20 shows the streamline diagram of the flow-pass sphere in the 3D flow field. For the details of the flow geometry and mechanical properties, the length X s of the recirculation region and the drag coefficient C d were selected to compare the simulation results with the previous results of A. Gilmanov et al [53] and Lei Xu et al [54] who adopted a general reconstruction algorithm with complex 3D immersed boundaries on Cartesian grids and a scalable parallel unstructured finite-volume LBM, respectively (see Figure 21). It can be concluded that as the Reynolds number increased, the recirculation region volume became larger, and the drag coefficient decreased.…”
Section: Flow Past a Sphere In Three-dimensionalmentioning
confidence: 99%